2022
DOI: 10.3389/fphar.2022.832789
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Trichilia catigua A. Juss. on DEHP-Induced Reproductive System Damage in Male Mice

Abstract: The present study aimed to explore the protective effect and molecular mechanisms of Trichilia catigua A. Juss. extract (TCE) against di (2-ethylhexyl) phthalate (DEHP)-induced damage to the reproductive system of mice. Acute toxicity tests revealed that the maximum tolerated dose (MTD) in mice was up to 2.7 g kg−1. After induction with DEHP, TCE (L-TCE, M-TCE, H-TCE) was orally administered to mice for 28 days. Differences in indicators among groups showed that TCE significantly improved the anogenital distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The acute toxicity of schaftoside in mice was evaluated 42 . Male ICR mice (20 g) were treated with schaftoside (20, 40, and 300 mg/kg, i.g.)…”
Section: Resultsmentioning
confidence: 99%
“…The acute toxicity of schaftoside in mice was evaluated 42 . Male ICR mice (20 g) were treated with schaftoside (20, 40, and 300 mg/kg, i.g.)…”
Section: Resultsmentioning
confidence: 99%
“…Similar to miR-375, PRPF3 may primarily regulate DEHP-induced reproductive toxicity, developmental toxicity, neurotoxicity, and metabolic toxicity. Under DEHP exposure, PRPF3 has the potential to cause germ cell growth arrest and dysfunction, abnormal neuronal cell metabolism, and hepatocyte apoptosis through regulation of genes related to the cell cycle and the ERK signaling pathway. Studies have shown that the regulation of HNF4α by PRPF3 may be involved in the regulation of intestinal transcription factors in the zebrafish gut flora to obtain adaptive immunity in DEHP exposure. , PRPF3 likely promoted carcinogenesis through activation of the JAK2/STAT3 signaling pathway in response to DEHP exposure. , In addition, the DEHP-induced disruption of glucose metabolism was likely to be regulated by PRPF3 as well. In this investigation, we demonstrated that the expression of PRPF3 , which is increased by DEHP exposure, could be detected at an environmental concentration as low as 2 μg/L.…”
Section: Discussionmentioning
confidence: 99%
“…Positive results are indicated by brown-yellow regions (Figure 7a), suggesting antigen antibodies binding to liver cells. The average density was determined by dividing the integrated optical density value (IOD) by the pixel area (AREA) of each positive image, allowing for the analysis of immunohistochemical findings through the mean density (AOD) for protein quantification [25]. Figure 7b-d Positive results are indicated by brown-yellow regions (Figure 7a), suggesting antigen antibodies binding to liver cells.…”
Section: Role Of Lrm In Nrf2 Ho-1 Nf-κb and Tnf-αmentioning
confidence: 99%